1987
DOI: 10.1103/physrevlett.59.839
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the abundance and coupling of cosmic axions at 4.5<ma<5.0 μeV

Abstract: We report preliminary results from a search for galactic axions in the frequency range 1.09 < f a < 1.22 GHz. For an axion linewidth V a < 200 Hz we obtain the experimental limit (g arr /m a ) 2 pa <1.4xl0" 41 . The theoretical prediction is (g ar y/m a ) 2 p a = 3.9x 10 ~4 4 with p a =300 MeV/cm 3 . We have also searched for the presence of a continuous spectrum of light pseudoscalar particles; if we assume that the above p a is contained between the upper and lower frequencies of our search, then we find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
200
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(202 citation statements)
references
References 20 publications
2
200
0
Order By: Relevance
“…On top of a T p,cavity of 0.1 K, quantum-noise-limited superconducting amplifiers were employed as the 1st amplifiers whose noise temperatures are proportional to not only the frequencies (T n,amp ∼ hν/k B ln 2) [28] but also the ambient temperatures (T p,cavity in axion haloscopes) to achieve fast DFSZ scanning rates from the small AC-TION experiment. Figure 5 shows the exclusion limits expected from the large and small ACTION experiments, and therein the exclusion limits from RBF [12], UF [13], ADMX [14,15], HAYSTAC [16], and CAST [22] are also shown.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…On top of a T p,cavity of 0.1 K, quantum-noise-limited superconducting amplifiers were employed as the 1st amplifiers whose noise temperatures are proportional to not only the frequencies (T n,amp ∼ hν/k B ln 2) [28] but also the ambient temperatures (T p,cavity in axion haloscopes) to achieve fast DFSZ scanning rates from the small AC-TION experiment. Figure 5 shows the exclusion limits expected from the large and small ACTION experiments, and therein the exclusion limits from RBF [12], UF [13], ADMX [14,15], HAYSTAC [16], and CAST [22] are also shown.…”
Section: Figmentioning
confidence: 99%
“…Assuming the axions have an isothermal distribution, the signal power given in Eq. (1) would then distribute over a Maxwellian shape with an axion rms speed of about 270 km/s in our galaxy [11], which is the basic model considered in this paper.Most of the axion haloscope searches to date [12][13][14][15][16] have employed a cylindrical resonator without an open resonator [17]. In this paper, we report the first axion haloscope search with toroidal geometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sikivie [3] suggested that relic axions could be detected through their conversion to photons in a resonant cavity bathed in a strong magnetic field. Experiments of this sort, which rely on the assumption that axions form a significant component of the galactic halo, have yet to confirm the presence of axions [4]. Attempts to produce axions and detect their * hep-ph/9502256, submitted to Phys.…”
mentioning
confidence: 99%
“…He suggested that this method can be used to detect the hypothetical galactic axion flux that would exist if axions were the dark matter of the Universe. Various terrestrial experiments to detect invisible axions by making use of their coupling to photons have been proposed [6,7,8], and the first result of such experiments appeared recently [9].…”
mentioning
confidence: 99%